2020
DOI: 10.1186/s12879-020-05210-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing the regulatory framework in South Africa – a single-blind randomized pilot trial of commercial probiotic supplementation to standard therapy in women with bacterial vaginosis

Abstract: Background: Bacterial vaginosis (BV) increases HIV risk and adverse reproductive outcomes. Standard-of-care (SOC) for BV are antibiotics; however, cure rates are low. Probiotics for vaginal health may be useful in improving cure and recurrence although the regulatory framework governing probiotics and the conduct of randomized clinical trials to evaluate these has not been established in South Africa. We performed an exploratory single-blind trial evaluating a commercial oral-vaginal-combination probiotic as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…Funnel plots suggested the heterogeneity between those studies. (Figure 3) G1: Fourteen randomized controlled trials [24][25][26][27][28][29][30][31][32][33][34][35][36][37] compared the e cacy of probiotic-assisted antibiotic therapy for BV with antibiotics alone (or plus placebo), including data from 1662 patients with BV. The cure rate was 72.98% (624/855) in the antibiotics + probiotics group and 62.70% (506/807) in the antibiotics (+placebo) group, with P = 0.009, reaching a statistically signi cant difference.…”
Section: Meta-analysis Of Treatment E Cacymentioning
confidence: 99%
“…Funnel plots suggested the heterogeneity between those studies. (Figure 3) G1: Fourteen randomized controlled trials [24][25][26][27][28][29][30][31][32][33][34][35][36][37] compared the e cacy of probiotic-assisted antibiotic therapy for BV with antibiotics alone (or plus placebo), including data from 1662 patients with BV. The cure rate was 72.98% (624/855) in the antibiotics + probiotics group and 62.70% (506/807) in the antibiotics (+placebo) group, with P = 0.009, reaching a statistically signi cant difference.…”
Section: Meta-analysis Of Treatment E Cacymentioning
confidence: 99%
“…G1: Fourteen randomized controlled trials [ 19 , 24 – 36 ] compared the efficacy of probiotic-assisted antibiotic therapy for BV with antibiotics alone (or plus placebo), including data from 1662 patients with BV. The cure rate was 72.98% (624/855) in the antibiotics + probiotics group and 62.70% (506/807) in the antibiotics (+placebo) group, with P = 0.009, reaching a statistically significant difference.…”
Section: Resultsmentioning
confidence: 99%
“…Although previous studies indicated that oral probiotics could contribute to the recovery of the vaginal microbiota and that probiotic species or strains could be detected in the vagina after oral probiotic administration (Anukam et al, 2006;Vujic et al, 2013;Heczko et al, 2015;Macklaim et al, 2015;Russo et al, 2018), contrary views still exist (Happel et al, 2020;Husain et al, 2020). A recent study from Reid et al demonstrated that oral intake of L. rhamnosus GR-1 and L. reuteri RC-14 did not change the vaginal microbiota significantly in low-risk pregnant women through the assessment of both Nugent Gram stain scoring and high-throughput sequencing (Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Although previous studies indicated that oral probiotics could contribute to the recovery of the vaginal microbiota and that probiotic species or strains could be detected in the vagina after oral probiotic administration ( Anukam et al., 2006 ; Vujic et al., 2013 ; Heczko et al., 2015 ; Macklaim et al., 2015 ; Russo et al., 2018 ), contrary views still exist ( Happel et al., 2020 ; Husain et al., 2020 ). A recent study from Reid et al.…”
Section: Discussionmentioning
confidence: 99%